2004
DOI: 10.1097/01.inf.0000128782.20060.79
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Study on the Effect of Intrapartum Antibiotic Prophylaxis on Early Onset Group B Streptococcal and Escherichia coli Neonatal Sepsis in Australasia

Abstract: The increasing use of intrapartum antibiotics produced a steady decline in EOGBS disease in Australasia. There was also a trend to decreasing EO E. coli sepsis in all babies, and the rate in very low birth weight infants remained stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 24 publications
4
81
5
2
Order By: Relevance
“…Western Pacific Angstetra et al 65 Daley et al 66 May et al 67 Tiskumara et al 62 Tiskumara et al 62 Kim et al 68 Niduvaje et al 69 Subtotal (I 2 =54·7%, p=0·039)…”
Section: Eastern Mediterraneanmentioning
confidence: 99%
“…Western Pacific Angstetra et al 65 Daley et al 66 May et al 67 Tiskumara et al 62 Tiskumara et al 62 Kim et al 68 Niduvaje et al 69 Subtotal (I 2 =54·7%, p=0·039)…”
Section: Eastern Mediterraneanmentioning
confidence: 99%
“…Specifically, questions have been raised regarding whether IAP results in higher incidences of EOS attributable to organisms other than GBS and whether it is associated with changes in rates of EOS caused by ampicillin-resistant organisms, particularly in VLBW infants. 2,[17][18][19][20][21][22] Our study is the largest single-center study of exclusively inborn neonates to address these questions. We found that the overall incidence of neonatal EOS decreased in the era of GBS IAP, among all newborns and among VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…These at-risk women are given intravenous antibiotics in labour to inhibit the transmission (Royal Australian and New Zealand College of Obstetricians and Gynaecologists, 2012; Reingold et al, 2007). As a result of intrapartum antibiotic prophylaxis, the incidence of early onset neonatal GBS disease in Australasia fell from 1.43 per 1000 live births in 1993 to 0.25 per 1000 live births in 2001 (Daley & Isaacs, 2004). However, there are disadvantages associated with the use of intravenous antibiotics.…”
Section: List Of Figuresmentioning
confidence: 99%
“…The disadvantages of giving intravenous antibiotics in labour include the development of antibiotic resistance in GBS and other bacteria, and the disruption of the early growth of good bacteria in the newborn's gut (Baltimore, 2007;Centers for Disease Control and Prevention, 2010;Cheng et al, 2006;Daley & Isaacs, 2004;Edwards, 2006;Grimwood et al, 2002;Ohlsson & Shah, 2013;Pattern et al, 2006;Rautava et al, 2012;Russel & Murch, 2006). In the United States and Canada, 20 to 35 per cent of labouring women now receive intravenous antibiotic prophylaxis (Baltimore, 2007;Centers for Disease Control and Prevention, 2010;Chen et al, 2005;Glasglow et al, 2005;Pattern et al, 2006).…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation